Penerapan Problem Based Learning dalam Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMA - Sukmayanti, Mimih (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2015)
The main purpose of this research is to compare the student mathematics problem solving ability ofsenior secondary school (SMA) students who received problem based learning, with those whoreceived exporitory learning. This research was based on fact that the student mathematics problemsolving ability of the secondary school student in SMAN 1 Pagaden were not good enough. Themethod used is mix method with Concurrent Embedded Eksperimental Model with Classroom actionresearch.The Subject in this research was SMA students from grade XI MIPA classes majoring inscience, from SMAN 1 Pagaden Subang. The instrumens were: Mathematics problem solving abilitytest, learning motivation questionnaire, student attitude scale and observation sheet. Summaries basedon the analysis were: (1) Problem Based Learning model can improve student mathematics problemsolving; (2) learning motivation of students have Problem Based Learning is better; (3) Students whoreceived Problem Based Learning model have higher mathematics problem solving ability than thosewho received expository learning; (4) Students who received Problem Based Learning model havehigher learning motivation than those who received expository learning; (5) There is a correlationbetween learning motivation and student mathematics problem solving ability; (6) the activity of thestudents who recieved Problem Based Learning is better. In general, Problem Based Learning could beconsidered as one of mathematics learning alternative in order to increase student mathematicsproblem solving ability.